1980
DOI: 10.1037/0012-1649.16.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Children's distributive justice reasoning: A standardized and objective scale.

Abstract: A paired-comparisons measure of distributive justice development (DJS) was developed and validated in three studies. In Study 1 104 children from kindergarten and second and fourth grades were given the DJS and two Piagetian logical reasoning tasks. Age trends and a relation with logical reasoning were found. In Study 2 66 children from first, third, and fifth grades were given the DJS and a measure of verbal ability. Age trends and a low relation with verbal ability were found. In Study 3 88 first, third, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 13 publications
1
33
0
1
Order By: Relevance
“…Altruism, therefore, can increase with age, in line with a realization of the consequences of oneÕs actions (Piaget, 1932(Piaget, /1977Keil, 1986). Damon (1975Damon ( , 1980) described a series of stages of ''positive justice'' understanding spanning the ages from 4 to 9 and beyond, and his views were subsequently supported by others (Enright, Franklin, & Manheim, 1980;McGillicuddy-De Lisi, Watkins, & Vinchur, 1994). In the present study, we are not concerned with the ethical level of the children, but in their ability to differentiate between moral and economic considerations, and to focus selectively on economic mechanisms when asked.…”
Section: Resultsmentioning
confidence: 93%
“…Altruism, therefore, can increase with age, in line with a realization of the consequences of oneÕs actions (Piaget, 1932(Piaget, /1977Keil, 1986). Damon (1975Damon ( , 1980) described a series of stages of ''positive justice'' understanding spanning the ages from 4 to 9 and beyond, and his views were subsequently supported by others (Enright, Franklin, & Manheim, 1980;McGillicuddy-De Lisi, Watkins, & Vinchur, 1994). In the present study, we are not concerned with the ethical level of the children, but in their ability to differentiate between moral and economic considerations, and to focus selectively on economic mechanisms when asked.…”
Section: Resultsmentioning
confidence: 93%
“…Previous research has shown that kindergarten children view allocations based on age entitlement as more fair than do older children (for example, Damon, 1977;McGillcuddy-De Lisi et al, 1994). But the effects of the age of the recipients on young children were interpreted often as children's tendency to justify fairness on the basis of external, observable realities, and were judged as an irrelevant basis for allocating resources (Damon, 1977;Enright et al, 1980). The results of this study provided more information about the effects of the age of recipients on children's concept of distributive justice.…”
Section: Discussionmentioning
confidence: 93%
“…Damon (1975Damon ( , 1977Damon ( , 1980) developed a cognitive-developmental method of positive justice reasoning and incorporated this developmental progression. This model was supported by other studies (for example, Enright, Enright and Lapsley, 1981;Enright, Franklin and Manheim, 1980;Enright et al, 1984). But these studies have only focused on specific kinds of merits of the recipients (e.g., being productive), without considering other types of merits that may affect children's decisions.…”
Section: Introductionmentioning
confidence: 94%
“…This theory provides an explanation of the experimental results discussed above. Support for this theory was provided by Enright et al (1984) and Enright et al (1980) for American, School Grade Offer (% of stake offered to responder) Murnighan and Saxon (1998) Harbaugh et al (2003) current study Fig. 2.…”
Section: Economic Socialisation Moral Development and Ultimatum Bargmentioning
confidence: 85%